Halal tourism: literature synthesis and direction for future research - Muhamad, Nur Sa'adah; Sulaiman, Syahnaz; Adham, Khairul Akmaliah; Said, Mohd Fuaad (2017)
Halal tourism is defined as the use or engagement of any object or action by Muslim travellers that conforms to the Islamic teachings or facilitates the practice of the religion. It is one of the latest trends that arises from the growth in the numbers of Muslim travellers world-wide and the rapid development of halal industry. The application of halal concept covers all aspects of tourism that cater to Muslim travellers’ needs, including its development and marketing, and this must be guided by the Islamic teachings and principles. Thus, this study’s objective is to analyse the current state of knowledge and practice of halal tourism. To achieve this objective, we reviewed the extant literature on halal tourism that have been published in high-tier academic journals. Based on the review, emergent themes on halal concept and its relation to tourism are discussed and the knowledge gap for future research is identified. We find that the halal tourism industry is booming, with an increase of interest among non-Muslim majority countries in attracting Muslim tourists. However, there seems to be variations on the practice of halal tourism, perhaps due to the complexity in serving different markets. Based on our analysis, implementation of halal tourism by Muslim-minority countries, such as Japan and New Zealand poses as the most pressing issue because of the need to ensure that the process and product complies with the requirements of Islamic teachings; while at the same time, to fulfil the need in developing and marketing halal tourism in those countries. Understanding implementation in this context is an important agenda for future research because of the need to ensure that the halal tourism services satisfy the fundamental issue of Muslims’ obligations to adhere to the Islamic teachings in all aspects of their life including while travelling.